Konstruksi Sosok Single Mother dalam Film yang Tak Tergantikan - Jennifer Lexandra; Nani Kurniasari (UNIVERSITAS KALBIS, 2022)
In the film Yang Tak Tergantikan the single mother figure is seen which is predominantly the important figure in the life of a family. This research was done to determine the single mother's construction contained in the film Yang Tak Tergantikan using a constructive paradigm. This research was researched using qualitative approaches and the theory of social reality construction in the Mass Media and also using semiotic analysis Charles Sanders Peirce, which had three significant elements: sign, object, and interpreter. The research found that there were thirteen single mothers who were constructed in a film Yang Tak Tergantikan. Among them are a critical and calm minded mother, a mother who thinks about her child's future, a hard-working mother who will fight for her children, a strong mother who will make her child a friend for discussion, a gentle and wise mother, a mother who forgives and does not judge her child, a mother who would realize her mistake and protector for her children.